2019
DOI: 10.1016/j.oneear.2019.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Hydro-socio-ecological Relationships to Enable More Integrated and Inclusive Water Allocation Planning

Abstract: Highlights d We used a transdisciplinary approach to support more inclusive water planning d We developed a hydro-socio-ecological model to underpin water allocation decisions d We propose principles for using e-flows to protect biodiversity and Indigenous values

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 65 publications
(117 reference statements)
4
61
0
1
Order By: Relevance
“…1a, Supplement Table S1). Most macroinvertebrates exhibited highly negative δ 13 C values between − 30 to − 33 ‰, suggesting they obtained their energy from terrestrial carbon sources and/or phytoplankton (Fig. 1a, Supplement Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1a, Supplement Table S1). Most macroinvertebrates exhibited highly negative δ 13 C values between − 30 to − 33 ‰, suggesting they obtained their energy from terrestrial carbon sources and/or phytoplankton (Fig. 1a, Supplement Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…We found little evidence that large-bodied fish contained remote carbon. However, our ability to investigate an energy subsidy from the floodplain to the main-channel was hampered by overlapping algal biofilm δ 13 C values in these two habitats. For instance, a Kruskal-Wallis rank sum test revealed that δ 13 C values for algal biofilm were similar in floodplain and main-channel habitats (Kruskal-Wallis χ 2 = 0.240, df = 1, p = 0.624).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations